Quantitative unit classification of ventral tegmental area neurons in vivo - Li, Wei (American Physiological Society, 2012)
Neurons in the ventral tegmental area (VTA) synthesize several major neurotransmitters, including dopamine (DA), GABA, and glutamate. To classify VTA single-unit neural activity from freely moving rats, we used hierarchical agglomerative clustering and probability distributions as quantitative methods. After many parameters were examined, a firing rate of 10 Hz emerged as a transition frequency between clusters of low-firing and high-firing neurons. To form a subgroup identified as high-firing neurons with GABAergic characteristics, the high-firing classification was sorted by spike duration. To form a subgroup identified as putative DA neurons, the low-firing classification was sorted by DA D2-type receptor pharmacological responses to quinpirole and eticlopride. Putative DA neurons were inhibited by the D2-type receptor agonist quinpirole and returned to near-baseline firing rates or higher following the D2-type receptor antagonist eticlopride. Other unit types showed different responses to these D2-type receptor drugs. A multidimensional comparison of neural properties indicated that these subgroups often clustered independently of each other with minimal overlap. Firing pattern variability reliably distinguished putative DA neurons from other unit types. A combination of phasic burst properties and a low skew in the interspike interval distribution produced a neural population that was comparable to the one sorted by D2 pharmacology. These findings provide a quantitative statistical approach for the classification of VTA neurons in unanesthetized animals.